Evaluation of radon levels in indoor gymnasia of Palermo (Sicily) and Sassari (Sardinia) (Italian Journal of Public Health, 2009)
Background: In the last decades, there has been increased worldwide interest in the management of healthrisks from indoor radon.Methods: From 2006 to 2008, a survey on air radon levels was carried out in a total of 57 indoor gymnasiarespectively located in the urban area of Palermo (Sicily) and Sassari (Sardinia).Results: The indoor radon levels were generally low with different geometric means in the two geographicareas (14.3 Bq/m3 in Palermo and 36 Bq/m3 in Sassari, respectively). Overall, in both groups increasingvalues of radon were found during the night and the early morning, with radon concentrations significantlylower during working time than at other times. The analysis of structural parameters showed that directcontact with the soil significantly correlated with increased levels of radon in gymnasia located in Palermo’sarea (p
Keywords: indoor radon; gymnasia; risk assessment